The Subjectivity of Consciousness as a Possible Theoretical Justification for Psychological Formative Context (FcDоC) in Children with Lowered Level of Consciousness - Bykova, V.I.; Vasilieva, I.D.; Lvova, E.A.; Fufaeva, E.V.; Valiullina, S.A. (Konsulʹtativnai͡a︡ psikhologii͡a︡ i psikhoterapii͡a, 2024)
Relevance. Currently, the issue of restoring consciousness after severe brain injury is a very acute one. Purpose. To present a new practical psychological technique, based on modern theoretical concepts of consciousness - Formative context in disorders of consciousness (FcDоC), which allows to dynamically change and form mental processes in decreased consciousness in children after severe brain injury. Material and methods. 4 children (aged 5-10 y.o.) with decreased level of consciousness after severe traumatic brain injury were enrolled in the pilot study at early stages of rehabilitation. Each child was shown a video about him/her which was shot a few days earlier. The film was accompanied by psychological comments, and child's reactions were simultaneously video recorded. Results were assessed with quantitative (SCAB) and qualitative techniques (visual observation, video recording). Results. All children demonstrated an emotional response after watching the film; there were marked positive changes in their psychic activity (less latent response time, better emotional and motor reactions). Conclusion. A new technique of psychological work with children in lowered level of consciousness after brain injury, which allows to form and restore child's mental capabilities, has been called «Formative context in disorders of consciousness (FcDоC)». The present study combines theoretical prerequisites of new knowledge on human consciousness formation with true practical experience. Актуальность. Тема восстановления сознания после тяжелых повреждений головного мозга в современном мире стоит очень остро. Цель данного исследования - на основе современных теоретических знаний о сознании представить новый практический психологический метод - формирующий контекст (Formative Context in Disorders of Сonsciousness, FcDоC), позволяющий изменять и формировать психические новообразования в ситуации сниженного сознания у детей после тяжелых повреждений головного мозга. Материалы и методы. В пилотажном исследовании участвовали 4 ребенка (5-10 лет), находящиеся в сниженных состояниях сознания после тяжелых повреждений головного мозга на ранних этапах реабилитации. Каждому ребенку демонстрировался видеоматериал о нем самом, отснятый днем ранее. Показ сопровождался психологическими комментариями и одновременной видеофиксацией реакций ребенка. Результаты оценивались количественным (Шкала коммуникативной активности В.И. Быковой (SCAB)) и качественным методами (включенное наблюдение, видеофиксация). Результаты. У всех детей был получен эмоциональный отклик на просмотр видеофильма о себе, а также достаточно быстро и значимо начали отмечаться положительные изменения в психической активности (уменьшение латентного времени ответов, увеличение эмоциональных и двигательных реакций). Заключение. Метод психологической работы с детьми в сниженном сознании после повреждений головного мозга, позволяющий формировать и восстанавливать психические возможности ребенка, получил название Формирующего контекста в сниженном сознании (Formative context in disorders of сonsciousness (FcDоC). Данное исследование позволяет соединить теоретические предпосылки относительно нового знания по формированию сознания с действенной тканью непосредственного практического опыта.